2017
DOI: 10.3390/app7101097
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection and Classification of Ulcerated Lesions Using Statistical Analysis for WCE Images

Abstract: Abstract:Wireless capsule endoscopy (WCE) is a technology developed to inspect the whole gastrointestinal tract (especially the small bowel area that is unreachable using the traditional endoscopy procedure) for various abnormalities in a non-invasive manner. However, visualization of a massive number of images is a very time-consuming and tedious task for physicians (prone to human error). Thus, an automatic scheme for lesion detection in WCE videos is a potential solution to alleviate this problem. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Figure 1 gathers the results from the previously presented studies, which focus on the ulcer detection. Suman et al [55] reported the best results compared to the other methods, achieving an accuracy of 97.9%. However, the results cannot be directly compared to the other methods because different datasets were used.…”
Section: Ulcer Detection Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 1 gathers the results from the previously presented studies, which focus on the ulcer detection. Suman et al [55] reported the best results compared to the other methods, achieving an accuracy of 97.9%. However, the results cannot be directly compared to the other methods because different datasets were used.…”
Section: Ulcer Detection Methodsmentioning
confidence: 95%
“…In this context, the majority of recent studies were based on combinations of texture and colour fea-tures to discriminate ulcers from normal tissues. In the study of Suman et al [55], the colour components of seven different colour spaces were analysed in order to find an optimal combination of their colour components that better discriminates ulcers from normal tissues. The selected components were Cr (which represents the difference of red from a reference value) from YCb-Cr colour space, the yellow (Y) component from CMYK colour space, and the blue (B) component from RGB.…”
Section: Ulcer Detection Methodsmentioning
confidence: 99%
“…In our previous work, we have developed an algorithm to extract color feature for ulcer using statistical feature analysis. 23 .…”
Section: Related Workmentioning
confidence: 99%
“…In [22], Suman et al reported their work on medical image processing for wireless capsule endoscopy. They introduced a novel statistical approach to differentiating ulcer and non-ulcer pixels using color bands as the feature vector and the support vector machine with grid search as the classifier.…”
Section: Smart Medicinementioning
confidence: 99%